2020
DOI: 10.14393/sn-v32-2020-56162
|View full text |Cite
|
Sign up to set email alerts
|

Poluição atmosférica: estudo de caso do Município de São Luís do Maranhão

Abstract: As capitais brasileiras têm apresentado problemas ambientais atmosféricos de diversas ordens, repercutindo negativamente na qualidade de vida de seus habitantes. São Luís, capital do estado do Maranhão, com uma população de mais de 1 milhão de habitantes constitui um bom exemplo de capital brasileira que também convive com problemas ambientais atmosféricos. A pesquisa ao analisar a poluição atmosférica da cidade de São Luís procurou também correlacionar com seus aspectos geográficos (físicos e humanos) por ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…However, the urban expansion of the city was not considered, which should be an important indicator to highlight possible locations for the installation of new monitoring stations. In another study on an average city, Pinheiro et al (2020) concluded that winds and precipitation, in addition to the size of the input source, were determinants for the worsening of air quality, which corroborate the conclusions of the present study.…”
Section: Number Of Stationssupporting
confidence: 91%
“…However, the urban expansion of the city was not considered, which should be an important indicator to highlight possible locations for the installation of new monitoring stations. In another study on an average city, Pinheiro et al (2020) concluded that winds and precipitation, in addition to the size of the input source, were determinants for the worsening of air quality, which corroborate the conclusions of the present study.…”
Section: Number Of Stationssupporting
confidence: 91%